A fenomenologia existencial de Minata, mãe educadora de aluno cego devido doença rara - Lima, Hedlamar Fernandes Silva (2023)
The general purpose of this doctoral thesis was to understand “what is it” and “how does it feel like” to be a mother-educator of a pupil with a rare disease, who became blind and who is under medical and educational assistance at both hospital and home. As a qualitative research, this writing has the existential phenomenology as its methodological basis, being its center: the human existence and the senses given by the Being – subject – within – the world, starting from its own life experiences. The phenomenology science was a fundamental and relevant method in order to achieve the comprehension of experiences. Ever since, this investigation, for the way it is the world, displays the complexity of interpersonal and psychological experiences that the mother felt in the way while following her son, since the space – time of the phenomenon is characterized by the Being- in – itself and by the Being – for – itself. More specifically, this writing relied on the work of some writers such as Rollo May (1909-1994) and Paulo Freire (1921 – 1997), whose thoughts allowed intensity and structure to our work, since both writers perceive the Being in the world as well. Even though here are some differences concerning the philosophical origin of both writers, persists the construction of rigorous knowledge, as ours, in dialogue with the thoughts of Freire and May, both concerning the human and social realm. The instruments used here were brought from the experiences collected during conversations based on empathy, images, video calls, WhatsApp messages and informal talks that took place during in loco visits (in and out of the hospital). The mother, whose fictitious name is Minata, has as fundamental mark of her existence the bravery to overcome the deep anguish in charge, and she does it through the joy and hope, surpassing all limitations of the environment where she lives, forcing herself to transform and transcend whenever is possible. This mother allows herself to be fully described by “what is it” and “how does it feel like” to be who she is, highlighting ways of being real and concrete, thus reveling a sad human being, while still there is a hopeful joy which completes and intensifies itself, facilitating the appearance of what became the mother-educator of a disabled child.